1971
DOI: 10.1073/pnas.68.7.1623
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Activity and Toxicity of Salts of Inorganic Group IIIa Metals: Aluminum, Gallium, Indium, and Thallium

Abstract: The Since gallium is a bone-seeking element (1-3), radionuclides of this element have been of clinical interest as diagnostic screening agents of bone tumors. In 1969 Edwards and Hayes (4) noted that carrier-free gallium-67 citrate was localized in addition in nonosseous tumors in patients with Hodgkin's disease and other lyinphomas. Deposition of this radioactive salt was also observed in patients with other "soft-tissue", slow-growing tumors (4-8), such as poorly differentiated thyroid adenocarcinoma, reticu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
1

Year Published

1974
1974
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(57 citation statements)
references
References 5 publications
0
56
0
1
Order By: Relevance
“…Although previous reports have indicated that surface transferrin receptor density on HL-60 cells decreases during DMSO treatment (21,33) and that this decrease may precede by 24 In additional experiments, we studied the effect of agents that we hypothesized would be more specific in affecting transferrin receptor expression. Previous studies have shown that radioactive gallium was taken up avidly by certain tumors (41), and the use of gallium salts as an antitumor agent had been suggested a number of years ago (42). More recent studies suggest that the addition of transferrin potentiates gallium salt-mediated arrest of cellular proliferation (36), an effect that may be related to inhibition of iron uptake (37).…”
Section: Resultsmentioning
confidence: 99%
“…Although previous reports have indicated that surface transferrin receptor density on HL-60 cells decreases during DMSO treatment (21,33) and that this decrease may precede by 24 In additional experiments, we studied the effect of agents that we hypothesized would be more specific in affecting transferrin receptor expression. Previous studies have shown that radioactive gallium was taken up avidly by certain tumors (41), and the use of gallium salts as an antitumor agent had been suggested a number of years ago (42). More recent studies suggest that the addition of transferrin potentiates gallium salt-mediated arrest of cellular proliferation (36), an effect that may be related to inhibition of iron uptake (37).…”
Section: Resultsmentioning
confidence: 99%
“…The intraperitoneal LD50 for Al(NO3)3 9H2O was reported to be 0.32 g/kg in male PBF1 mice and 0.33 g/kg in female Sprague-Dawley rats (481,482). The oral LD50 in rats has been reported to be 0.26 g/kg (176).…”
Section: Toxicology Of Aluminum and Its Compoundsmentioning
confidence: 99%
“…Regarding inorganic Ga compounds, it was observed that only the Ga 3+ cation has toxic activity. Thus, comparing the action of sulphates and chlorides, similar cytotoxic effects were evidenced [96].…”
Section: Data Concerning Biomedical Effectsmentioning
confidence: 67%